Kinematically optimal robust control of redundant manipulators - Galicki, Mirosław (Zielona Góra: Uniwersytet Zielonogórski)
This work deals with the problem of the robust optimal task space trajectory tracking subject to finite-time convergence. Kinematic and dynamic equations of a redundant manipulator are assumed to be uncertain. Moreover, globally unbounded disturbances are allowed to act on the manipulator when tracking the trajectory by the end-effector.
Keywords: redundant robotic manipulator; task space trajectory tracking; robust optimal finite-time control; Lyapunov stability